OPEN QUESTIONS ON CEPHEIDS AND THEIR PERIOD-LUMINOSITY RELATIONSHIP - Szabados, L. (Одеські астрономічні публікації, 2010)
Physical properties and pulsational behaviour of classical Cepheids can be studied in unprecedented details based on recent photometric and spectroscopic data. In spite of important new results, problems related to Cepheids still exist, such as metallicity dependence of their various properties, their mass loss and circumstellar environment, excitation of low-amplitude pulsation modes in such variables, etc.